Validation of the oral impact on daily performance frequency scale in Ibadan, Nigeria (2013)
Background: Oral health related quality of life measures provide alternative ways to evaluate oral health status in a way that prioritises impact on lifestyle. These measures are, however, hardly used in our setting. Before the measures can be used effectively, validity of the tool needs to be evaluated. The aim of the study was to validate the Oral Impact on Daily Performance (OIDP) frequency scale in an adult Nigerian patient population. Methodology: This was a descriptive cross sectional study in which consecutive patients attending the Primary Oral Health Care Centre, Idikan and the Oral Diagnosis Clinic of the University College Hospital, Ibadan were recruited. Data was collected with OIDP structured interviewer administered questionnaires, global self-rating and perceived treatment need questions and by oral examination. The frequency scale of the OIDP index was used to compute the impact scores. Data collected was subjected to statistical analysis using SPSS version 19. Results: A total of 204 patients participated in the study. The OIDP score ranged from 0 to 40; 78.9% of the participants reported an impact on daily performance with eating and enjoying food being the most reported activity impacted upon. The Cronbach’s alpha coefficient was 0.811; the OIDP index was significantly associated with global self ratings of oral health, perceived need for dental treatment and was able to discriminate between patients with or without dental caries. Conclusion: The OIDP frequency scale exhibited satisfactory psychometric properties amongst adult dental patients in Ibadan, Nigeria